The Application of Literary Theories in Literary Texts - Ferianda, Sandy (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2017)
This research mainly focused on discovering the application of literary theory in literary texts. Literary theories and literary texts were the same as two sides of a coin. They could not be separated or segregated. In addition, they both also helped people or the readers understand the application of them. However, even though literary theory and literary texts were interrelated or interconnected, they both shared different concept. Literary theory referred to on this basis, a set of assumptions or principles in which they could be used to explain, criticize, and interpret particular aspects, situations, or conditions in literary texts. Whereas, literary text, to some extent, referred to a created story in which it was based on people’s experience such as novels, poems, and many others. The method used in this research was the library research or library studies in which the data were gathered through reading literatures and taking important notes. The primary and secondary data were used to analyze the study. The primary source was some of the literary theories in the literary works such as novel and short stories. The secondary source was gathered through reading journals, articles, and books. The findings of the study referred to four main theories, namely, structuralism, post-structuralism, post-modernism, and psychoanalysis. The application of structuralism theory in literary texts gave some insights which showed that although a thing had its structure that shape or form, it is still standing a single unity. It also happened to the literary works. Even though a literary work had its structure, it was still seen as a unity eventually. The application of post-structuralism theory showed that in reading a literary text, one might had different interpretation toward it. One might say A, but the other would probably say B. However, it was rather difficult to have the same interpretation as what the author of the texts really wanted to say without referring it to another related source to help people understand and be able to do certain analysis. The application of post-colonialism theory in literary text showed that the post-colonial theorist entered the literary texts or works through a specific critical lens, or a specific way of reading them. That critical lens, post-colonial theory or post-colonialism, asked the reader to analyze and explain the effects that colonization and imperialism, or the extension of power into other nations, had on people and nations. The last theory, the application of psychoanalysis theory in literary text showed that this theory was not the only theory that people could use to analyze or criticize the characters in literary works or texts. It might be possible if one wanted to use this theory to reveal what is intended by the author or what the characters’ motivations were. Key words: Literary theory, literary text.